Prophetic Parenting and the Crisis of Fatherlessness: Lessons from Ibrahim and Jacob in Tafsir al-Kasyaf - Mukholifah, Siti; Surur, Aziz Miftahus (Universitas Muhammadiyah Surakarta, 2026)
The phenomenon of fatherlessness has emerged as a significant global social issue, influ-encing children's psychological well-being, identity formation, and moral development. While existing scholarship has largely examined fatherlessness through psychological and sociological frameworks, Qur'anic narratives on father-child relationships are often treated primarily within theological discourse. Consequently, there remains limited explo-ration of how classical Qur'anic exegesis can contribute to contemporary discussions on parenting and family crises. Addressing this gap, this study investigates the concept of paternal parenting in the stories of Prophet Ibrahim and Prophet Ya'qub through the in-terpretive lens of Tafsir al-Kashshāf by al-Zamakhsharī and examines its relevance to the modern phenomenon of fatherlessness. This research employs a qualitative library-based approach combined with thematic Qur'anic interpretation (tafsīr mawḍū'ī). The analysis focuses on key Qur'anic passages related to father-son interactions, particularly Q.S. al-Ṣāffāt:102 and Q.S. Yūsuf:4-5, interpreted through the linguistic-rational framework characteristic of Tafsir al-Kashshāf. Data are analyzed descriptively and interpretatively to identify the parenting principles embedded within the exegetical discourse. The find-ings demonstrate that Tafsir al-Kashshāf articulates a prophetic model of paternal parent-ing grounded in three interrelated principles: democratic companionship, dialogical com-munication, and secure emotional attachment. Prophet Ibrahim's interaction with Ismail il-lustrates participatory decision-making and consultative dialogue, while Prophet Ya'qub's relationship with Yusuf reflects emotional attentiveness and psychological protection that foster a secure relational environment. This study contributes to Qur'anic studies by highlighting the contemporary relevance of classical exegesis in addressing modern social challenges. Furthermore, it offers a conceptual framework for integrating Qur'anic parent-ing values into contemporary family discourse, emphasizing the father's emotional pres-ence, communicative engagement, and moral leadership as essential elements in mitigating the fatherlessness crisis in modern societies.